A New Type of aContra Continuous Functions - Amirthalingam, V.; Vijayarakavan, M. (International Journal of Engineering and Technology, 2018)
In this article, the author present the another class of functions which is called a contra generalized - continuous function in Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â topological spaces. A few portrayals and properties identified with contra - continuous functions are to be obtained.Â Â Â